1995
DOI: 10.2307/2136175
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Peer Communication Effects on AIDS-Related Behavior Among U.S. High School Students

Abstract: Data from a 1989 national probability sample of 8,098 high school students in the United States indicate that young people's discussions about the human immunodeficiency virus (HIV) with parents and with peers are highly correlated and have opposite effects on behavior. Students who discussed HIV with their parents were less likely than those who did not to have had multiple sex partners, to have had unprotected sexual intercourse and to have ever injected drugs; on the other hand, students who discussed HIV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 31 publications
2
82
3
1
Order By: Relevance
“…Findings suggest that parent-child communication about condom use was not a significant predictor of condom use and that peer communication about condom use was only a marginally significant predictor, which is not consistent with the findings of prior studies by Holtzman and Rubinson (1995) and by Jaccard and Dittus (1993). One possible explanation is that parental and peer communications might become less influential for students when compared with their earlier stages of development.…”
Section: Predictors Of Condom Usecontrasting
confidence: 88%
See 2 more Smart Citations
“…Findings suggest that parent-child communication about condom use was not a significant predictor of condom use and that peer communication about condom use was only a marginally significant predictor, which is not consistent with the findings of prior studies by Holtzman and Rubinson (1995) and by Jaccard and Dittus (1993). One possible explanation is that parental and peer communications might become less influential for students when compared with their earlier stages of development.…”
Section: Predictors Of Condom Usecontrasting
confidence: 88%
“…For example, a number of studies showed that parent-child communication about sexual issues is associated with delayed onset of sexual intercourse (e.g., Aspy et al, 2007;Lehr, DiIorio, Dudley, & Lipana, 2000), increased contraceptive use (including condom use), and fewer sexual partners (e.g., Holtzman & Rubinson, 1995;Pick & Palos, 1995).…”
Section: Theoretical Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that each year, worldwide, 15 million girls aged 15-19 years give birth and that about (11%) of children are born to adolescents [10]. Each year, more than 1 million teenagers become pregnant and (65%) of the resulting babies are born out of wed lock [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on a sample of 8,098 high school students, adolescents who discussed Human Immunodeficiency Virus (HIV) with their parents were less likely to have had multiple partners, unprotected sex, or to have injected drugs than did those who did not discuss HIV with their parents (Holtzman & Rubinson, 1995) [7]. Similarly, Luster and Small (1994) [8] found that low-risk females, defined as those who had only one partner and always used contraception, were more likely to report having discussed birth control with their mothers than were those defined as high-risk, defined as those who had multiple partners and never or rarely used contraception.…”
Section: Parent-adolescent Communication About Sexualitymentioning
confidence: 99%